Validity and Reliability of Wii Fit Balance Board for the Assessment of Balance of Healthy Young Adults and the Elderly - Chang, Wen-Dien (The Society of Physical Therapy Science, 2013)
[Purpose] Balance is an integral part of human ability. The smart balance master system (SBM) is a balance test instrument with good reliability and validity, but it is expensive. Therefore, we modified a Wii Fit balance board, which is a convenient balance assessment tool, and analyzed its reliability and validity. [Subjects and Methods] We recruited 20 healthy young adults and 20 elderly people, and administered 3 balance tests. The correlation coefficient and intraclass correlation of both instruments were analyzed. [Results] There were no statistically significant differences in the 3 tests between the Wii Fit balance board and the SBM. The Wii Fit balance board had a good intraclass correlation (0.86–0.99) for the elderly people and positive correlations (r = 0.58–0.86) with the SBM. [Conclusions] The Wii Fit balance board is a balance assessment tool with good reliability and high validity for elderly people, and we recommend it as an alternative tool for assessing balance ability.